HOUSEHOLDS’ FOOD CONSUMPTION BEHAVIOUR DURING COVID-19 PANDEMIC: EVIDENCE FROM RURAL HOUSEHOLDS IN SOUTH AFRICA - Lefophane, Hilda; Mkasi, Felicity Ntombikayiso; Lefophane, Mapula Hildah (Applied Studies in Agribusiness and Commerce, 2023)
The food consumption behaviour of households has been affected by the lockdown restrictions that were implemented to reduce the COVID-19 infection rate. This study was aimed at analysing the food consumption behaviour of rural households during the COVID-19 pandemic in South Africa. To achieve this, a simple random technique was used to collect data from 120 in Merry Pebble (MP) Stream Village. Thereafter, an Ordered Probit Model was used to examine the extent to which households have increased, decreased or maintained the same quantity of food consumed during COVID-19. The results indicated that 46.7% of the rural households had consumed less food during COVID-19 pandemic, 32.5% consumed about the same amount of food, and 20.8% consumed more food. The variables that contributed towards a decrease in food consumption are employment status, household size, loss of income, and social relief grants. On the contrary, bulk buying and food parcels had stabilised food consumption, while the number of employed people in a household and food bought from restaurants contributed towards an increase in food consumption during COVID-19 pandemic. With regard to consumption behaviour per food item, fresh produce, meat, snacks and fast food were consumed less during COVID-19, while there was a constant consumption in dairy products, and an increase in consumption of canned food, frozen food, prepared food, grains and water. The study recommends that the government should continue with the economic and social relief programmes that were created during COVID-19, as they play an important role in increasing and stabilising food consumption by rural households.